THE ROLE OF EDUCATION IN FORMING DIGITAL ETHICS AND SUPPORTING ACADEMIC HONOR - ZAKRYZHEVSKA, Iryna; OVOD, Larysa (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In today's society, characterized by rapid digitalization and technological development, education becomes a key element of adaptation for both students and teachers to new realities. Digital tools open up new opportunities for improving the educational process, and also contribute to the development of professional and digital skills necessary for future specialists in various fields. The use of digital technologies in education allows creating an interactive environment where students can actively participate in the process of acquiring knowledge and forming competencies that meet the requirements of the modern labor market.In the course of writing a scientific article, the main attention is paid to the study of the role of education in the formation of digital ethics and the maintenance of academic integrity in the conditions of modern digital transformation. The work revealed that digital ethics, which covers the protection of personal data, respect for copyright and avoidance of data manipulation, is critical for ensuring responsible behavior in the digital environment. The impact of digital technologies on academic integrity is explored, including issues arising from plagiarism, data fabrication, and plagiarism, and the role of educational institutions in preventing these violations is analyzed. The importance of integrating modern digital tools, such as plagiarism checking systems and platforms for managing scientific sources, into the educational process as a means of supporting academic integrity is separately analyzed. In the context of rapid digitalization, it is determined that the formation of digital ethics through educational institutions is the basis for maintaining high standards of scientific activity and the ethical use of digital technologies.
Keywords: digital ethics; ethical use; academic integrity; higher education; plagiarism; artificial intelligence; innovative technologies